2021
DOI: 10.3389/fcimb.2021.744049
|View full text |Cite
|
Sign up to set email alerts
|

A New Biomarker of Fecal Bacteria for Non-Invasive Diagnosis of Colorectal Cancer

Abstract: BackgroundThe intestinal flora is correlated with the occurrence of colorectal cancer. We evaluate a new predictive model for the non-invasive diagnosis of colorectal cancer based on intestinal flora to verify the clinical application prospects of the intestinal flora as a new biomarker in non-invasive screening of colorectal cancer.MethodsSubjects from two independent Asian cohorts (cohort I, consisting of 206 colorectal cancer and 112 healthy subjects; cohort II, consisting of 67 colorectal cancer and 54 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…For microbiome-derived biomarkers based on bacteria for the detection of early CRC, 26 articles were found and two articles were found investigating the co-metabolome solely as a biomarker. Seventeen of the studies were conducted in East Asia [ 19 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ], one in South Asia [43] , eight in Europe [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] and two in North America [ 52 , 53 ]. The number of inclusions of these studies ranged between 2 and 462 for CRC, 18 and 665 for adenoma and/or polyp and 24 and 788 for healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For microbiome-derived biomarkers based on bacteria for the detection of early CRC, 26 articles were found and two articles were found investigating the co-metabolome solely as a biomarker. Seventeen of the studies were conducted in East Asia [ 19 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ], one in South Asia [43] , eight in Europe [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] and two in North America [ 52 , 53 ]. The number of inclusions of these studies ranged between 2 and 462 for CRC, 18 and 665 for adenoma and/or polyp and 24 and 788 for healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…The number of inclusions of these studies ranged between 2 and 462 for CRC, 18 and 665 for adenoma and/or polyp and 24 and 788 for healthy controls. Regarding the stage used in the articles for early CRC detection, five studies were based on stage I or II [ 29 , 30 , 37 , 40 , 50 ] and two used stage 0 [ 19 , 38 ]. The other studies investigated a precursor lesion of CRC, either advanced adenomas or polyps (AP) [ 28 , [31] , [32] , [33] , [34] , [35] , 39 , 41 , [44] , [45] , [46] , [47] , [48] , [49] , [51] , [52] , [53] ].…”
Section: Resultsmentioning
confidence: 99%
“…In early 2001, Ramon et al reported the association of G. morbillorum and colon cancer [35]. A recent work of Yao et al identified G. morbillorum as one of the non-invasive biomarkers of CRC from gutMEGA database [36]. E. hallii is a common gut microbe with probiotic properties regard to intestinal metabolic balance as contributing to propionate formation [37].…”
Section: Taxonomy Profiling Metadatamentioning
confidence: 99%
“…It is also one of the most abundant species in numerous types of systemic abscesses, and it exhibits a surprisingly strong association with a variety of malignant tumors ( 4 7 ). In fact, P. micra has even been proposed as a discriminating biomarker for colorectal cancer, gastric cancer, and oral cancer ( 4 , 8 , 9 ). In the oral cavity, P. micra exists as a low-abundance species during oral health but is highly enriched in periodontitis lesions and infected root canals and is especially prevalent in polymicrobial odontogenic abscesses ( 10 15 ).…”
Section: Introductionmentioning
confidence: 99%